A Case Study on Chunghwa Picture Tubes (Malaysia) Sdn. Bhd. - Yil, Kiong Ung (1997)
The success of business organizations depends highly on the various decisions made by the management at the strategic level like products decision, financing decision and human resource decisions. This case is prepared with the purpose of looking into the internal factors, industry factors and. general environments' factors affecting an organization that should be considered in decisions making at the top management level. Part I of this paper presents the information on the internal and external aspects of the organization. Part II of this paper presents analysis on the internal and external factors. Alternative courses of actions, evaluation and recommendations are then given for strategic decisions making for the organization based on the analysis performed.